"Focus on getting MVPs out onto the market": EPIC CTO interview with Mostafa Afgani. Issue 6 (27th November 2022) - Unknown
Abstract: EPIC's photonics technology manager Ivan Nikitskiy talks to Mostafa Afgani, CTO and co‐founder at PureLiFi, a developer and innovator of Li‐Fi technology.